Determinação da perda d'água por percolação e por Runoff em irrigação por sulco - Bernardo , Salassier (Revista Ceres, 2025)
Mathematical equations for the computation of deep percolation and runoff are presented. The equations express the percentages of deep percolation and runoff as a function of the length of each sector, the exponent of the accumulated infiltration equation, the length of the furrow and the factor R (ratio of the time of application and time necessary for the flow to reach the end of the furrow). These equations yield good results as shown by comparison with the Bishop equation for two field data. The greater the number of intervals in which the time of advance is divided, the more precise will be the calculation of percentage of percolation.